2021
DOI: 10.46265/genresj.pybz4246
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic erosion on Ethiopian tetraploid wheat landraces using different approaches

Abstract: The demand and use of improved crop varieties by farmers has increased in the central highlands of Ethiopia, where continuous loss of local traditional varieties has been occurring in the last two to three decades. The objectives of the study were to assess the extent of genetic erosion and perception of farmers and associated causes for the reduction of traditional farmers' varieties. Direct field assessment covering 56 wheat farms and a survey in which 149 farmers participated were carried out in three distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The number of farmers cultivating landraces and their relative area coverage were determined. The number of landraces cultivated recently as compared to the previous number was the basis for the calculation of genetic erosion [ 15 , 47 , 48 ]. A reduction in richness (that is a reduction in the total number of crops, varieties or alleles) is a better indicator for genetic erosion, as it does recognize the dynamics in the system [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of farmers cultivating landraces and their relative area coverage were determined. The number of landraces cultivated recently as compared to the previous number was the basis for the calculation of genetic erosion [ 15 , 47 , 48 ]. A reduction in richness (that is a reduction in the total number of crops, varieties or alleles) is a better indicator for genetic erosion, as it does recognize the dynamics in the system [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Direct field observations provided the first lines of evidence for genetic erosion. Local knowledge, gathered through interviews with farmers and their families, community meetings, and surveys, have been widely used to assess change and document farmers’ perspectives [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has led to an alarming rate of genetic erosion. Alemayehu et al (2021) reported that, on average, 75.8% genetic erosion was observed in tetraploid wheat after 25 years based on direct farm assessments and survey studies in Lume, Adaa, and Chefe, respectively. The lowest genetic erosion was observed at Chefedonsa, which is found in the highlands of Shoa.…”
Section: Introductionmentioning
confidence: 99%